Integrating UAV Data and Community Knowledge for Optimal Tsunami Evacuation Route Map in Coastal Loto Village, Ternate - Amelia, Risky Nuri; Ningrum, Rohima Wahyu; Robo, Tamrin; Ikhsan, Muhammad; Triani, Triani; Aswan, Marwis; Safitri, Yuni Andriyani; Rakuasa, Heinrich (Universitas Negeri Medan, 2025)
The coastal area of Ternate Island has a high potential for tsunami disasters and complex tectonics. The tsunami on Ternate Island was triggered by an earthquake in the Maluku Sea and the eruption of Mount Gamalama under the sea. The rapid development of Ternate, especially in the tourism sector, such as Loto Agrotourism Village, West Ternate, demands attention to the safety of visitors and residents. The main problem in Loto Village is the lack of evacuation routes, so an effective evacuation strategy is needed to minimize losses during a tsunami disaster. This study aims to determine evacuation routes using UAV data and participatory mapping in Loto Village, Ternate City. UAV aerial photos were processed using photogrammetry techniques with Agisoft Metashape Professional software, producing Ortho-Mosaic Maps and Digital Elevation Model (DEM), which were analyzed in QGIS software. The ortho-mosaic map was overlaid with a tsunami hazard map to create temporary evacuation routes and points (TES), which were confirmed through participatory mapping. The Final Map shows four TESs, which are accessible via footpaths, side roads, and main roads. In the event of a tsunami, tourists and residents in the Lota Agrotourism area can use this map for evacuation. The map can also be an important reference for the government in forming disaster mitigation policies to ensure the safety of tourist destinations that are vulnerable to tsunamis.